2016
DOI: 10.3892/br.2016.825
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma free amino acid profiles in canine brain tumors

Abstract: Abstract. Canine brain tumors are best diagnosed using magnetic resonance imaging (MRI). However, opportunities of MRI examination are restricted due to its limited availability in veterinary facilities; thus, numerous canine brain tumors are diagnosed at an advanced stage. Therefore, development of a noninvasive diagnostic biomarker is required for the early detection of brain tumors. In the present study, plasma free amino acid (PFAA) profiles between dogs with and without brain tumors were compared. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Metabolites, including amino acids, can be altered in both neoplastic tissues 23,24 and plasma. 7,[10][11][12][13][14][15][16]18 Alterations in amino acid profiles and protein metabolism can reflect the effect of pathogenic changes because tumor development and growth require amino acids for protein synthesis, and both local and circulating amino acids are critical sources of metabolic fuel, leading to an increase in the mass of the affected tissue. 11,23 Previous studies in humans have suggested that some amino acids and liver function indicators, including Fischer's ratio and BTR, are associated with HCC metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites, including amino acids, can be altered in both neoplastic tissues 23,24 and plasma. 7,[10][11][12][13][14][15][16]18 Alterations in amino acid profiles and protein metabolism can reflect the effect of pathogenic changes because tumor development and growth require amino acids for protein synthesis, and both local and circulating amino acids are critical sources of metabolic fuel, leading to an increase in the mass of the affected tissue. 11,23 Previous studies in humans have suggested that some amino acids and liver function indicators, including Fischer's ratio and BTR, are associated with HCC metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy is a technique for sampling and analyzing non-solid biological tissues, and is mainly used to diagnose disease or monitor therapy. Serum or plasma compounds such as VEGF, glial fibrillary acidic protein, plasma free amino acid profiles, and CSF concentrations of uric acid, D-dimers, and MMP-2 and MMP-9 have been quantified in dogs with brain tumors, but results to date suggest that these compounds will not fulfill ideal biomarker criteria due to limitations associated with sensitivity and specificity (5965).…”
Section: Diagnosis Of Intracranial Tumorsmentioning
confidence: 99%
“…The present case showed increased 18F-FDOPA metabolism and revealed strongly diffuse immunoreactivity for LAT1. In veterinary medicine, immunoreactivity for LAT1 in meningiomas was evaluated in only two dogs and two brain samples showed negative or weakly positive reactions for LAT1, previously (28). This is the first case in canine meningioma to show marked immunoreactivity for LAT1, 18F-FDOPA uptake, and suggests that LAT1 may be a molecular target for diagnostic PET imaging and a therapeutic target for canine meningioma.…”
Section: Discussionmentioning
confidence: 74%